Highly Efficient Broadband Light Absorber Based on Nonuniform Hyperbolic Metamaterial Film - Nina A. Zharova; Alexander A. Zharov; Alexander A. Zharov (Advances in Condensed Matter Physics)
We develop a concept of highly efficient broadband light absorber based on nonuniform hyperbolic metamaterial. We suggest a gradual bending of the anisotropy axis inside the metamaterial that results in spatial shift of the area of resonant absorption depending on the incidence angle. In this resonant region the wavevector of light is parallel to the generatrix of resonant cone and the radiation losses are maximal because of extremely high value of refraction index. Changing the radiation frequency also shifts the spatial position of the resonant region so that high level of absorption may be achieved in wide frequency range. Using the model of nanowire medium (silver wires in silica host) we predict that 200 nm film of this hyperbolic metamaterial allows reaching almost total absorption of radiation throughout the visible band.